Relationship between swallow, support scale and iron cross on rings and their specific preconditioning strengthening exercises - Hübner, K.; Schärer, C. (Science of Gymnastics Journal, 2015)
International men`s gymnastics has evolved rapidly on all six apparatus. On rings, strength elements are primarily determining. Various preconditioning strengthening exercises are performed routinely in training. However, the relationship between these exercises and the strength elements on rings, which would be of interest for coaches, are not well studied. The objective of this study was to investigate the correlation between strength in seven preconditioning exercises and performance of three important hold elements: Swallow, Support Scale and Iron Cross. Ten male gymnasts of the Swiss national team performed a 1RM test for each of the seven strength exercises and a maximum static hold of the strength elements on rings. A significant correlation was observed only between Swallow with the preconditioning exercises Swallow supine position (r: 0.71, p: 0.031) and Bench press (r: 0.71, p: 0.046); as well as between Support Scale and Swallow supine position (r: 0.69, p: 0.039). Iron Cross correlated highest with the Cross belt (r: 0.66, p: 0.051) and Bench press (r: 0.67, p: 0.069). Further, it was observed that a minimal 1RM of 73.4% body weight is needed for the exercise Swallow supine position in order to complete a hold of the element Swallow on rings. For execution of the element Support Scale, a 1RM of 67.4% body weight for the exercise Swallow supine position is needed.